Religiusitas Dan Pencapaian Pendidikan Padamasyarakat Sumatera Barat - Wulandari; Julhadi; Rusydi AM (Qolamuna : Jurnal Studi Islam, 2024)
Religiosity is the dominant factor that determines the level of educational attainment in West Sumatra. Through literature study using the meta-analysis method of ten relevant international and national journals. Religiosity is seen as a potential factor influencing educational attainment in various cultural contexts, including in West Sumatra, which has a rich cultural and religious background. The meta-analysis method is used to integrate and analyse findings from various existing studies, with a focus on variables related to the level of religiosity of individuals or communities and their impact on educational attainment, such as academic achievement, learning motivation, and educational aspirations. The findings of this research are that religiosity factors influence educational attainment in West Sumatra, and there are implications for educational policy and social practice in the area. This research also provides a strong theoretical basis for further research in this area, and can be an important reference for decision makers in developing more inclusive and sustainable education strategies in Indonesia. Keywords : Religiosity, Education, West Sumatra.